2010
DOI: 10.1016/j.hrthm.2009.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Role of inflammation and oxidative stress in atrial fibrillation

Abstract: BACKGROUND Atrial fibrillation (AF) is the most common arrhythmia in clinical practice. There is increasing evidence that inflammation and oxidative stress contribute to the pathogenesis of AF, but their role remains poorly defined. Furthermore, it is unclear if inflammation and oxidative stress are associated with particular types of AF. OBJECTIVE The purpose of this study was to define the role of inflammation and oxidative stress in AF. METHODS Using a case-control study design, 305 patients with AF wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
234
1
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(254 citation statements)
references
References 34 publications
(26 reference statements)
8
234
1
11
Order By: Relevance
“…267 A follow-up secondary analysis of the participants Cardiovascular Health Study participants further revealed that elevated CRP predicted incident AF. 268 Subsequent studies have demonstrated relationships between several different serologic markers of inflammation and AF, including IL-6, 269 TNF-a, 270 aldosterone 271 and simple white blood cell counts. 272 Analyses of multiple inflammatory biomarkers within the same study have suggested that IL-6 and osteoprotegerin 273 may be especially important.…”
Section: Impact Of Atrial Cardiomyopathies On Occurrence Of Atrial Fimentioning
confidence: 99%
“…267 A follow-up secondary analysis of the participants Cardiovascular Health Study participants further revealed that elevated CRP predicted incident AF. 268 Subsequent studies have demonstrated relationships between several different serologic markers of inflammation and AF, including IL-6, 269 TNF-a, 270 aldosterone 271 and simple white blood cell counts. 272 Analyses of multiple inflammatory biomarkers within the same study have suggested that IL-6 and osteoprotegerin 273 may be especially important.…”
Section: Impact Of Atrial Cardiomyopathies On Occurrence Of Atrial Fimentioning
confidence: 99%
“…12 In the presumor necrosis factor-α (TNF-α) is a proinflammatory cytokine that has been implicated in the pathogenesis of a number of cardiovascular diseases, including acute myocardial infarction, heart failure, atherosclerosis and sepsisrelated cardiac dysfunction. 1, 2 In healthy individuals, the plasma and cardiac levels of TNF-α are both low, suggesting that TNF-α has little physiological importance in the normal heart.…”
mentioning
confidence: 99%
“…Several studies have demonstrated that PD, which is considered to be a risk factor for AF, is higher in patients with BD than control subjects (9, 10), AF and prolonged PD is related with ongoing inflammation and endothelial damage/dysfunction (32)(33)(34)(35). Like most of the vasculitic pathologies, inflammation, the endothelial damage and dysfunction are apparently associated with the etiopathogenesis of BD.…”
Section: Discussionmentioning
confidence: 99%